Dose calculation for electron therapy using an improved LBR method. Issue 7 (17th June 2013) - Gebreamlak, Wondesen T.; Tedeschi, David J.; Alkhatib, Hassaan A.
Abstract : Purpose: : To calculate the percentage depth dose (PDD) of any irregularly shaped electron beam using a modified lateral build‐up ratio (LBR) method. Methods: : Percentage depth dose curves were measured using 6, 9, 12, and 15 MeV electron beam energies for applicator cone sizes of 6 × 6, 10 × 10, 14 × 14, and 20 × 20 cm 2 . Circular cutouts for each cone were prepared from 2.0 cm diameter to the maximum possible size for each cone. In addition, three irregular cutouts were prepared. Results: : The LBR for each circular cutout was calculated from the measured PDD curve using the open field of the 14 × 14 cm 2 cone as the reference field. Using the LBR values and the radius of the circular cutouts, the corresponding lateral spread parameter [σ R ( z )] of the electron shower was calculated. Unlike the commonly accepted assumption that σ R ( z ) is independent of cutout size, it is shown that its value increases linearly with circular cutout size (R). Using this characteristic of the lateral spread parameter, the PDD curves of irregularly shaped cutouts were calculated. Finally, the calculated PDD curves were compared with measured PDD curves. Conclusions: : In this research, it is shown that the lateral spread parameter σ R ( z ) increases with cutout size. For radii of circular cutout sizes up to the equilibrium range of the electron beam, the increase of σ R ( z ) with the cutout size is linear. The percentage difference of the calculated PDD curve from the measured PDD data for irregularly shaped cutouts was under 1.0% in the region between the surface and therapeutic range of the electron beam. Similar results were obtained for four electron beam energies (6, 9, 12, and 15 MeV).